Total project control a practitioner's guide to managing projects as investments - Devaux, Stephen A., 1949- (Industrial innovation series, 2015)
There is often a deep disconnect between the project team's goals and those of the organization. Senior management wants "profitable" projects, but is only able to quantify its wishes in terms of the traditional project management elements: schedule and cost. To operate smoothly, the entire organization must be driven by the single goal of project profitability. Total Project Control presents valuable enhancements to the traditional project management approach, introducing new metrics and techniques for assessing the performance and profitability of projects.